2001
DOI: 10.1007/s002530100620
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of mercury from wastewater by genetically engineered Escherichia coli

Abstract: Genetically engineered E. coli, which express both a Hg2+ transport system and metallothionein, were tested for their ability to remove mercury from wastewater. The wastewater contained more than ten different ions, including 2.58 mg/l mercury, and its pH was 9.6. Mercury uptake was faster from the wastewater than from distilled water, probably because of the higher ionic strength, as the high pH had little effect on mercury accumulation. EDTA also stimulated mercury uptake rather than inhibiting it. A hollow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…One of the initial efforts to retain mercury in bacterial bioreactors was made by 7) Canstein et al 10) , who demonstrated the removal of mercury from chloralkali electrolysis wastewater by a mercury resistant Pseudomonas putida strain. A genetically engineered E. coli strain with a Hg 2+ transport system and metallothionein has been used to bioaccumulate mercury from wastewater 15) . There was a clear correlation between the amount of Cd taken up by the MRB and the amount of Cd removed from the medium.…”
Section: Discussionmentioning
confidence: 99%
“…One of the initial efforts to retain mercury in bacterial bioreactors was made by 7) Canstein et al 10) , who demonstrated the removal of mercury from chloralkali electrolysis wastewater by a mercury resistant Pseudomonas putida strain. A genetically engineered E. coli strain with a Hg 2+ transport system and metallothionein has been used to bioaccumulate mercury from wastewater 15) . There was a clear correlation between the amount of Cd taken up by the MRB and the amount of Cd removed from the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the use of heavy metal tolerant organisms have had some success in efficient bioaccumulation of high concentrations of heavy metals. These have been developed by adaptation in laboratories (de Siloniz et al 2002;Kocberber and Donmez 2007;Yilmazer and Saracoglu 2009), isolated from polluted environments (Kocberber and Donmez 2007) and by genetic engineering (Deng and Wilson 2001). Current studies on the efficacy of these organisms, however, have focused on the bioaccumulation of single metals.…”
mentioning
confidence: 99%
“…Their work demonstrated for the first time that these two mer transport proteins do not mistake other thiophilic metal ions such as Cd(II) for Hg(II) when exposed to both in a thiol-free phosphate buffer. Their system has been implemented in a hollow-fibre batch reactor (Deng & Wilson, 2001) with fast kinetics and high capacity for Hg(II) removal from dilute, oxidized systems such as urban wastewater. The third major contributors to this area, Wilfred Chen and his coworkers, have compared cytosolic, periplasmic and surface display of synthetic phytochelatins in E. coli (Bae et al, 2000(Bae et al, , 2001 and Moraxella (Bae et al, 2002) for their acquisition of Hg(II) by cells growing and being induced in minimal medium; they found surface expression to be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Because of potentially lower costs, higher efficiency and specificity, the use of micro-organisms and plants for sequestering the contaminating metals is currently receiving considerable attention (Chaney et al, 1997;Gadd, 2000;McIntyre, 2003). Several metal-binding proteins and peptides found in some of the bacterial metal resistance or plant and fungal metal tolerance systems have been engineered into plant and bacterial hosts for potential use in bioremediation (Bae et al, 2001(Bae et al, , 2002(Bae et al, , 2003Chen & Wilson, 1997a, b;Chen et al, 1998;Deng & Wilson, 2001;Kotrba et al, 1999b;Meagher, 2000;Mejare & Bulow, 2001;Sousa et al, 1996Sousa et al, , 1998Valls et al, 2000a, b;Vieira & Volesky, 2000). Our work extends these observations to include an engineered subdomain of the well-studied metalloregulator, MerR, and contrasts the quantitative performance of this construct with its free form, with its parent protein MerR both free and fused, and with other engineered bacterial metal-sequestering systems.…”
Section: Introductionmentioning
confidence: 99%